Enhanced optical and ragged metamaterials properties of silver silica nanocomposite thin film via sol-gel and electrophoresis deposition technique - Taib, Taifunisyam; Johan, Mohd. Rafie; Basirun, Wan Jefrey (Scientific Net, 2022)
Abstract. Various filling fractions of silver silica nanocomposites (Ag-SiO2 NC) were successfully synthesized via sol-gel technique and deposited onto indium tin oxide via electrophoretic deposition (EPD) for thin film applications. Ag-SiO2 NC was investigated using X-ray diffraction, FTIR spectroscopy, Uv-vis and transmission electron microscopy. The XRD and Uv-vis results revealed that Ag-SiO2 NC is stable with a filling fraction of 0.6 in the dielectric medium with excellent absorption peak. Spectroscopy Ellipsometry shows that the effective permittivity and refractive index obtained from this filling fraction are -0.88 and 0.90, respectively. A ragged of metamaterial properties at negative permittivity are also reported.